Development of Plumbing Work Practice Learning Videos In the Department of Civil Engineering Education and Planning UNY - Prihadi, Wisnu Rachmad; Santoso, Agus; Pratomo, Hasdi Nur (Indonesian Journal Of Civil Engineering Education, 2023)
This research contributes to (1) developing a learning video of Plumbing and Sanitation Practice Practice, (2) knowing the feasibility of the Plumbing and Sanitation Practice Practice video learning media, (3) knowing user perceptions regarding the Plumbing and Sanitation Practice Practice learning video applied to the Department of Education UNY Civil Engineering and Planning. This research is an R&D research with a 4D model approach (Define, Design, Development, Disseminate). Data collection techniques are based on research subjects in making video products for Plumbing practice learning videos, namely experts related to plumbing materials, media experts. The instrument used uses a Likert scale to measure the feasibility level of the product being developed. The results obtained are (1) the define stage, namely analyzing the initial conditions, analyzing the character of students, analyzing concepts and learning objectives, the design stage, namely designing a script for the delivery of information consisting of opening, content, closing, the development stage, namely the process of recording making a video learning until the completion of editing the resulting video and then testing the eligibility validation of the product by experts, the disseminate stage, namely the limited dissemination of the product produced in this case the learning video of plumbing work practices to samples to assess and find out the level of feasibility and usefulness of the product; (2) the level of product feasibility based on the material content made is worth 4.58 belonging to the "very feasible" category, while the assessment based on the media made is worth 4.91 belonging to the "very feasible" category; (3) The results of the disseminate that has been carried out obtain the value of the user's perception of the product which is included in the very high category, the percentage of product feasibility is 91.52% which is included in the "Very Eligible" category.